ANALISIS KELAYAKAN USAHATANI BUAH NAGA (HYLOCEREUS COSTARICANSIS) DI PEKANBARU (Studi di Kelurahan Sail Tenayan Raya Pekanbaru) - Khairunnas '; Ermi Tety (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
Horticulture crop have big enough role to increase produce and earnings of farmer.Dragon Fruit representing one of the new horticulture crop is conducting inIndonesia with fruit ruddle to blaze and is scaly of green. This research aim to toanalyse: Elegibility of Rhinoceros case study fragon fruit usahatani Sub-District OfSail District Of Great Tenayan of Town of Pekanbaru. This location is selectedintentionally with consideration of the area represent sentra produce red fragon fruitfirst time [in] Pekanbaru. Method Research the used is case study method byperforming a direct perception of leisure to one farmer people interview and alsonote document of activity of farming of red fragon fruit which done conducted. Datawhich is needed in this research consist of primary data and of sekunder. purposeof analysed by using analysis of criteria invesment which consist of NPV, IRR, NetB/C, PBP.